Struktur dan Fungsi Sosial Kepercayaan Rakyat Ungkapan Larangan Pada Masyarakat Jawa di Kenagarian Sungai Duo - Melia Safitri; M. Ismail Nasution (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
The expression of prohibition in Javanese society is one part of folklore. There are fewer and fewer speakers of people's beliefs nowadays, because today is a modern era so many people don't believe or don't know about these expressions anymore. Therefore, the research aims to maintain the traditions that have existed from ancient times so that the next generation can know these traditions. This research is a qualitative research using descriptive method. This research was conducted in Kenagarian Sungai Duo, Sitiung District, Dharmasraya Regency. Kenagarian Sungai Duo is divided into two jorongs, namely Jorong Koto Agung Kanan and Jorong Koto Agung Kiri. The entries in this study are folk beliefs about the prohibition against pregnancy, childbirth and childhood in the Javanese community. Dharmasraya Regency. The informants of this research are natives of the Javanese community in Kenagarian Sungai Duo, Sitiung District, Dharmasraya Regency. In this study, the research instrument was the researcher herself named Melia Safitri with NIM 18017110. The data in this study were oral tradition data in the form of expressions of folk beliefs about pregnancy, childbirth, and childhood in the Javanese community. Dharmasraya Regency. The technique used is the triangulation techniques in the process of validating the data. In terms of structure, found 28 data with a two-part structure and seven data with a three-part structure. From all research results found 30 data that has a prohibition function, 7 data that has a function as a thickener of religious emotions or beliefs, 6 data that has a function as an imaginary projection system, 5 data that has a commanding or reminding function and 6 data that has a function as an educational tool.